Influence of Spatial Ability on Students' Mathematical Representation Ability in the Spatial Geometry Course - Izzati, Nurma (MASI Mandiri Edukasi, 2024)
This research aims to 1) Determine the spatial mathematical abilities of students in the spatial geometry course, 2) Understand the mathematical representation ability of students in the spatial geometry course, and 3) determine the influence of spatial ability on students' mathematical representation ability in the spatial geometry course. The research method uses a quantitative method with a one-shot case study research design. The research population is all students of the Department of Mathematics of UIN Siber Syekh Nurjati Cirebon who take the spatial geometry course in the odd semester of the 2024/2025 Academic Year, which consists of 3 classes: A, B, and C. The research sample was selected from 30 students from the research population using a simple random sampling technique. The data collection technique uses tests to determine students' spatial mathematical ability and mathematical representation ability. The results of the study showed that: 1) the student's mathematical spatial ability in the spatial geometry course averaged 77.23, included in the strong category; 2) students' mathematical representation ability in the spatial geometry course averaged 82.77, included in the strong category; and 3) mathematical spatial ability has a significant effect on students' mathematical representation ability in the spatial geometry course. Mathematical spatial ability has a 67% influences on students' mathematical representation ability in spatial geometry courses.